In vitro activity of chemicals and commercial products against Saprolegnia parasitica and Saprolegnia delica strains. Issue 2 (10th December 2018) - Tedesco, Perla; Fioravanti, Maria Letizia; Galuppi, Roberta
Abstract: Oomycetes of the genus Saprolegnia are responsible for severe economic losses in freshwater aquaculture. Following the ban of malachite green in food fish production, the demand for new treatments pushes towards the selection of more safe and environment‐friendly products. In the present work, in vitro activity of ten chemicals and three commercial products was tested on different strains of Saprolegnia, using malachite green as reference compound. The compounds were screened in agar and in water to assess the minimum inhibitory concentration (MIC) and the minimum lethal concentration (MLC), respectively. Two strains of Saprolegnia parasitica and one isolate of Saprolegnia delica were tested in triplicate per each concentration. Among tested chemicals, benzoic acid showed the lowest MIC (100 ppm) followed by acetic acid, iodoacetic acid and copper sulphate (250 ppm). Sodium percarbonate was not effective at any tested concentration. Among commercial products, Virkon ™ S was effective in inhibiting the growth of the mycelium (MIC = MLC = 1, 000 ppm). Actidrox® and Detarox® AP showed MIC = 5, 000 and 1, 000 ppm, respectively, while MLCs were 10‐fold lower than MICs, possibly due to a higher activity of these products in water. Similarly, a higher effectiveness in water was observed also for iodoacetic acid.